Resultado fiscal estrutural: visões metodológicas e aplicações para o Brasil - Barros, Gabriel Leal de (2018)
After the beginning of the economic stabilization process, initiated just before and established by the Real Plan in 1994, there was a notable advance in 2000 with the introduction of the Fiscal Responsibility Law (LRF). The commitment fiscal policy rule in later years, through raising and sustaining the primary result, produced, complement to significant reductions of indebtedness, relative solace with the design of the country's fiscal institutions. With the outbreak of the international crisis in 2008, a period in which fiscal policy was use as a countercyclical instrument much has changed. The conventional fiscal statistics gradually lost relative importance due to a series of accounting issues that had an impact on public accounts. Non-recurring events grew both in quantity and in volume, affecting the economic agents perception regarding the effective fiscal position. The deceleration of post-crisis growth and the deep economic recession experienced in 2016 and 2017 expanded the magnitude of the worsening and deepened the fiscal imbalance of the country. During this period, several economic studies and international research were develop in order to improve the evaluation of the impact of fiscal policy, at which time the calculation of the fiscal result adjusted by the economic cycle gained more spotlight. Despite the different methodologies available for its measurement, empirical results point out that it can make more or less sense to adopt it as a modern rule of fiscal policy. From this perspective, its feasibility depends on a series of preconditions that reflect, in a sense, the degree of accountability, transparency, maturity and consensus of economic institutions and agents. From the point of view of the usefulness to estimate the fiscal impulse on the aggregate demand and inflation and, therefore, of the relation between the fiscal and monetary policies, its application is valuable.